2004
DOI: 10.1016/j.otohns.2004.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Controlled Clinical Trial of a Novel Matrix Hemostatic Sealant in Children Undergoing Adenoidectomy

Abstract: Floseal matrix hemostatic sealant is a safe, efficacious, easy, and cost-effective technique for obtaining hemostasis in children undergoing adenoidectomy. Limitations of the study include the fact that it is nonblinded, which does allow for some bias in the subjective data recorded. However, utilizing 4 different operating surgeons, 3 of whom were not affiliated with the study, minimized this. CLINICAL SIGNIFICANCE OF STUDY: This study demonstrates the safety and efficacy of a novel hemostatic sealant in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 13 publications
(26 reference statements)
1
48
0
Order By: Relevance
“…Binnetoglu et al [17] evaluated the use of TGHM in the case of secondary bleeding after tonsillectomy, particularly for patients with multiple sites of bleeding and/or an overcauterized tonsillar bed, confirming the effectiveness of this product as a means of achieving competent hemostasis. Jo and Mathiasen [18] and Mathiasen et al [19] prospectively assessed the use of this hemostatic matrix in children who underwent adenoidectomy and adenotonsillectomy, respectively. These authors found that the use of TGHM was associated with shorter operative times, less blood loss, and with decreased postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Binnetoglu et al [17] evaluated the use of TGHM in the case of secondary bleeding after tonsillectomy, particularly for patients with multiple sites of bleeding and/or an overcauterized tonsillar bed, confirming the effectiveness of this product as a means of achieving competent hemostasis. Jo and Mathiasen [18] and Mathiasen et al [19] prospectively assessed the use of this hemostatic matrix in children who underwent adenoidectomy and adenotonsillectomy, respectively. These authors found that the use of TGHM was associated with shorter operative times, less blood loss, and with decreased postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoidectomy is on e of the m ost co mmonly perf ormed p rocedures in children , but b leeding f ollowing adenoidectomy may pose a s a c hallenge to a surgeon and m ay require the pl acement of a post erior n asopharyngeal pack followed by a subsequent prolonged hospitalisation (Mathiasen and Cruz, 2004). Therefore, improvements in currently used techniques and innovations th at enable a m ore ef ficient bl eeding control dur ing and f ollowing adenoid ectomy would be welcomed.…”
Section: Discussionmentioning
confidence: 99%
“…Tradition al electrical and mechanical m eans are still the m ainstay of haemorrhage control, but new h aemostatic technologies continue to emerge (de la Torre et al, 2007). Mechanical and active topical sealants and haemostatic agents are now available in different forms; these agents can be used in a variety of settings as adjuncts to the control of surgical bleeding (Spotnitz et al, 2007;Jo et al, 2007;Mathiasen and Cruz, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Adenoidectomy is a common surgical procedure conducted throughout childhood, with nearly 300,000 cases annually [1]. Various adenoidectomy techniques have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that the average intraoperative hemorrhage during adenoidectomy is 43-54 ml. In the event that the hemorrhage exceeds 100 ml, the risk of postoperative complications increases [1].…”
Section: Introductionmentioning
confidence: 99%